Rational design of silicon structures for optically controlled multiscale biointerfaces. (July 2018) - Jiang, Yuanwen; Li, Xiaojian; Liu, Bing; Yi, Jaeseok; Fang, Yin; Shi, Fengyuan; Gao, Xiang; Sudzilovsky, Edward; Parameswaran, Ramya; Koehler, Kelliann; Nair, Vishnu; Yue, Jiping; et al.
Abstract Silicon-based materials have been widely used in biological applications. However, remotely controlled and interconnect-free silicon configurations have been rarely explored, because of limited fundamental understanding of the complex physicochemical processes that occur at interfaces between silicon and biological materials. Here, we describe rational design principles, guided by biology, for establishing intracellular, intercellular and extracellular silicon-based interfaces, where the silicon and the biological targets have matched properties. We focused on light-induced processes at these interfaces, and developed a set of matrices to quantify and differentiate the capacitive, Faradaic and thermal outputs from about 30 different silicon materials in saline. We show that these interfaces are useful for the light-controlled non-genetic modulation of intracellular calcium dynamics, of cytoskeletal structures and transport, of cellular excitability, of neurotransmitter release from brain slices and of brain activity in vivo. Intracellular, intercellular and extracellular silicon interfaces enable light-controlled non-genetic modulation of intracellular calcium dynamics, of cellular excitability, of neurotransmitter release from brain slices, and of brain activity in vivo.